The stingless bee species, Scaptotrigona aff. depilis, as a potential indicator of environmental pesticide contamination. (18th July 2015) - de Souza Rosa, Annelise; I'Anson Price, Robbie; Ferreira Caliman, Maria Juliana; Pereira Queiroz, Elisa; Blochtein, Betina; Sílvia Soares Pires, Carmen; Imperatriz‐Fonseca, Vera Lucia
Abstract: Neonicotinoids have the potential to enter the diet of pollinators that collect resources from contaminated plants. The species Scaptotrigona aff. depilis (Moure, 1942) can be a useful indicator of the prevalence of these chemicals in the environment. Using high‐performance liquid chromatography–mass spectrometry, the authors devised a protocol for neonicotinoid residue extraction and detected the presence of neonicotinoids in the bee bodies. Thus, the authors consider this species to be a potential indicator of environmental contamination. Environ Toxicol Chem 2015;34:1851–1853. © 2015 SETAC